Sprint acceleration biomechanics - Willwacher, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Sprint start performance (SSP) is of prime importance in short sprint races. The purpose of this workshop was to present a method for the evaluation of SSP in a typical training environment. For this purpose, starting blocks, instrumented with 3D force sensors in the front and the rear block were utilized in combination with high-speed video cameras and light barriers. Performance related parameters could be extracted immediately from the captured force signals. Individual values were compared to a large reference database. Comparisons were made to reference values of athletes with similar sprint performance capacity. Optimisation potentials in technical and strength related aspects of SSP were highlighted for each start, based on the actual overall sprinting performance level of the athlete.